Assessment of Problem Associated with the Ilam Urban Water Supply System of Nepal - Jha, Bibek; Dahal, Khet Raj; Parajuli, Ramesh (International Journal on Engineering Technology, 2025)
The Ilam urban water supply system in Nepal faces serious challenges that affect its efficiency and reliability. Many of the pipes and infrastructure are old and damaged, leading to frequent leaks and water wastage. Some areas do not get enough water, while others have too much, causing distribution problems. The Water Users’ Committee (WUC) also struggles financially because it does not receive enough support from the municipality. Due to this, it cannot afford proper maintenance or pay staff well, making it harder to keep the system running smoothly. Additionally, the recent shift to a new management system has created further issues, as poor knowledge transfer and resistance to change have disrupted daily operations and led to financial losses. To fix these problems, a comprehensive plan is needed. First, the infrastructure must be improved by using better materials, fixing leaks regularly, and adopting modern leak detection technology. Strengthening financial planning, creating a formal water management board, and ensuring proper training for staff will also help improve management and reduce disruptions. Proper planning for water demand and supply, along with risk assessment, is necessary to keep the system stable in the long run. By taking these steps, the Ilam water supply system can become more reliable, ensuring a steady and efficient water supply for the growing community.